The Incidence and Management of Urethral Stricture in Bladder Carcinoma - Ahmed Farhood , Reyad; Jasim Mohammed Alzaidy, Othman; Abd Al Hameed Hassen, Aiad (Diyala Journal of Medicine, 2021)
Background: Urethral stricture disease is one of the oldest and most difficult maladies known to the urologist. While references to the disease and its treatment date back to the writings of the Hindus, Egyptians, and Greeks. Objective: To elicit the incidence of urethral strictures, their severity and management in patients with superficial bladder tumor. Patients and Methods: From January 2018 to January 2020, we followed 98 patients admitted and treated at Baquba Teaching Hospital urology unit for having bladder carcinoma. Theywere all male subjects, their age range from 38-76y with a mean 56.8y. They were required to have a cystoscopically and histologically proven superficial transitional cell carcinoma of the bladder to be enrolled in this study (invasive tumors were excluded). For all the patients and after having the cystoscopic diagnosis ,transurethral resection of the tumor done and in most of them this is followed by six week courses of intravesical chemotherapy (either mitomycin or doxorubicin according to the availability). Intravesical Doxorubicin used in 13 cases (56.5%), Mitomycin C in 6 cases (26.1%) and 3 patients (13.0%) received both drugs (through multiple courses).while 1 patient (4.3%) received no chemotherapy. Thirteen strictures (56.5%) were managed by optical urethrotomy while 10 cases (43.5%) were mild strictures and opened just by introducing the cystoscope. Results: During the period of the study, a total of 23 urethral strictures were identified in the 98 male patients with superficial bladder tumor enrolled in this study, which constitutes an incidence of 23.5% all were diagnosed by the follow -up check cystoscopies . Patient age ranged from 38-75 years with a mean age 59.30+- 10.58 . Among those patients with urethral stricture ,14 patients had also B.P.H (60.9%), but only 7 patients (30.4%) had a history of retention of urine . The urethral stricture was bulbar in all patients and it was mild stricture in 10 cases (43.5%), moderate in 6 cases (26.1%) and severe in 7 cases (30.4%) . Prior to the diagnosis of stricture , 13 patients had been subjected to a single check cystoscopy (56.5%) ,6 patients (26.1%) had twice , while 4 patients (17.4%) had 3 or more cystoscopies prior to the occurence of stricture . Regarding intravesical chemotherapy prior to the occurance of stricture ,4 patients (17.4%) received 1-3 sessions , 10 patients (43.5%) received 4-6 sessions and 9 patients (39.1%) received more than 6 sessions . Intravesical Doxorubicin used in 13 cases (56.5%), Mitomycin C in 6 cases (26.1%) and 3 patients (13.0%) received both drugs (through multiple courses).while 1 patient (4.3%) received no chemotherapy. Thirteen strictures (56.5%) were managed by optical urethrotomy while 10 cases (43.5%) were mild strictures and opened just by introducing the cystoscope. Conclusion: Urethra stricture in patients with bladder carcinoma may be a substantial source of preventable morbidity, implementing a nursing education program may significantly decrease the incidence of stricture.